2004
DOI: 10.1038/sj.mp.4001605
|View full text |Cite
|
Sign up to set email alerts
|

Association and linkage of α-2A adrenergic receptor gene polymorphisms with childhood ADHD

Abstract: Attention-deficit hyperactivity disorder (ADHD) is a heritable disorder, prevalent from childhood through adulthood. Although the noradrenergic (NA) system is thought to mediate a portion of the pathophysiology of ADHD, genes in this pathway have not been investigated as frequently as those in the dopaminergic system. Previous association studies of one candidate gene in the NA system, ADRA2A, showed inconsistent results with regard to an MspI polymorphism. In the current study, two nearby single-nucleotide po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
3
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 41 publications
(38 reference statements)
5
69
3
2
Order By: Relevance
“…Our evidence suggests that a decrease in α2-adrenergic autoreceptor control of NE activity underlies noradrenergic hyperfunction in our rat model of prenatal cocaine, so it is interesting that a similar deficit appears to occur in the spontaneously hypertensive rat model of ADHD (Russell, 2002) and that a decreased density and decreased affinity of binding to α2-adrenergic sites have been reported in ADHD (Shekim et al, 1994;Deupree et al, 2006). Moreover, there is evidence supporting association and linkage of α2A-adrenergic receptor gene polymorphisms with ADHD (Park et al, 2005).…”
Section: Discussionmentioning
confidence: 91%
“…Our evidence suggests that a decrease in α2-adrenergic autoreceptor control of NE activity underlies noradrenergic hyperfunction in our rat model of prenatal cocaine, so it is interesting that a similar deficit appears to occur in the spontaneously hypertensive rat model of ADHD (Russell, 2002) and that a decreased density and decreased affinity of binding to α2-adrenergic sites have been reported in ADHD (Shekim et al, 1994;Deupree et al, 2006). Moreover, there is evidence supporting association and linkage of α2A-adrenergic receptor gene polymorphisms with ADHD (Park et al, 2005).…”
Section: Discussionmentioning
confidence: 91%
“…However, studies involving Western populations have reported that the G allele of the MspI polymorphism and the T allele of the DraI polymorphism in ADRA2A are putative risk alleles in ADHD. 30,31 Ethnic differences in allele frequencies may be responsible for the discrepancies between populations, 29 and there is also a possibility that the pattern of linkage disequilibrium might differ among populations. 32 Divergent results among studies might also reflect methodologic issues, such as sample size, inclusion or exclusion criteria, or instruments used to assess symptom characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, genetic studies have turned to genes associated with norepinephrine transmission. The norepinephrine synthetic enzyme dopamine beta hydroxylase (DBH) and the gene encoding for the a2A adrenoceptor have been associated with ADHD (Roman et al, 2003;Park et al, 2005). It should be noted that the D4 receptor has very high affinity for norepinephrine (Van Tol et al, 1991) and should really be considered a catecholamine receptor.…”
Section: Genetics Of Adhd: Focus On Catecholaminesmentioning
confidence: 99%